1985
DOI: 10.1002/bbpc.19850890112
|View full text |Cite
|
Sign up to set email alerts
|

Interlamellar Liquid Sorption on Hydrophobic Silicates

Abstract: A particular advantage of adsorption measurements on layer silicates is that the adsorption between the silicate layers can be followed by X‐ray measurements. — When the external and internal surface of the silicate montmorillonite is modified by increasing amounts of hexadecylpyridinium cations, the surface character changes from hydrophilicity to hydrophobicity. The changes are evaluated from the excess adsorption isotherms for methanol‐benzene mixtures. The volume Vs of the adsorption phase derived from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
1

Year Published

1986
1986
2011
2011

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(9 citation statements)
references
References 8 publications
2
6
1
Order By: Relevance
“…The surface excess isotherms for ethanol/cyclohexane are type-II isotherms (Schay-Nagy classification, Kipling, 1965). In contrast to similar isotherms observed for the Na form of montmorillonite (Dékány et al, 1985;Berger et al, 1997) the linear section of the composite isotherms did not extent to x 1 = 1; the deviation was more pronounced at higher Al contents.…”
Section: R E S U L T Scontrasting
confidence: 74%
See 2 more Smart Citations
“…The surface excess isotherms for ethanol/cyclohexane are type-II isotherms (Schay-Nagy classification, Kipling, 1965). In contrast to similar isotherms observed for the Na form of montmorillonite (Dékány et al, 1985;Berger et al, 1997) the linear section of the composite isotherms did not extent to x 1 = 1; the deviation was more pronounced at higher Al contents.…”
Section: R E S U L T Scontrasting
confidence: 74%
“…Introducing poly(hydroxoaluminium) pillars into Namontmorillonite changed the hydrophilic/hydrophobic character of the internal and external surfaces. The degree of hydrophilicity was deduced from adsorption experiments using binary liquid mixtures (Dékány et al, 1985(Dékány et al, , 1986aDékány, 1992). When a mixture of two liquids with different polarity, e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although sydration behavior of original montmorillonite has been extensively studied in past two decades [25][26][27][28][29], less attention has been paid to the structural characteristics of wet OMt [30][31][32]. Several previous reports indicated that X-ray diffraction (XRD) is still the most widely used method for characterizing the structure of OMt in water, and the results showed that water molecules can always cause evident swelling of OMt [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…When the originally hydrophilic surface is modified by long alkyl chains [80][81][82][83][84][85][86][87][88][89][90][91][92], heats of immersion display significantly greater differences. This is well demonstrated by adsorption and X-ray diffraction measurements in toluene (Table 5).…”
Section: Heat Of Wetting On Swelling Clay Mineralsmentioning
confidence: 99%